2000
DOI: 10.1111/j.1469-445x.2000.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐Converting Enzyme Genotype Affects the Response of Human Skeletal Muscle to Functional Overload

Abstract: The response to strength training varies widely between individuals and is considerably influenced by genetic variables, which until now, have remained unidentified. The deletion (D), rather than the insertion (I), variant of the human angiotensin‐converting enzyme (ACE) genotype is an important factor in the hypertrophic response of cardiac muscle to exercise and could also be involved in skeletal muscle hypertrophy – an important factor in the response to functional overload. Subjects were 33 healthy male vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(48 citation statements)
references
References 13 publications
6
40
0
2
Order By: Relevance
“…In keeping with this hypothesis, modulation by genetic variants of the skeletal response induced by strenuous exercise has previously been reported 16,17 . By expressing exon 18 alleles in the context of their haplotype in vitro, we found the T variant to be associated with a significantly decreased response to canonical Wnt3a signaling.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In keeping with this hypothesis, modulation by genetic variants of the skeletal response induced by strenuous exercise has previously been reported 16,17 . By expressing exon 18 alleles in the context of their haplotype in vitro, we found the T variant to be associated with a significantly decreased response to canonical Wnt3a signaling.…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, there is some evidence that genetic variation may influence the response of muscles and the skeleton to intense physical training. 16,17 Recently, mutations in the lipoprotein receptor-related protein 5 (LRP5) gene have been demonstrated to result in different single gene disorders with either a high or low BMD phenotype 18 . Thus in the autosomal recessive disorder, osteoporosis-pseudoglioma syndrome (OPPG), very low bone mass and blindness have been linked to loss-of-function mutations in the LRP5 gene.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects with the ID and DD genotypes improved their quadriceps muscle strength 97% and 66% more than did the subjects with the II genotype, respectively. 11 Folland and colleagues 11 speculated that the ACE genotype that regulates hypertrophic responses in other tissues has a similar effect in skeletal muscle. The D allele has been associated with higher systemic 28 and cardiac tissue 29 ACE activities.…”
Section: Ace and Strength Performancementioning
confidence: 99%
“…31,32 The interaction of ACE in the same fashion in skeletal muscle may represent a possible mechanism for the greater strength gains associated with the D allele. 11 However, hypertrophy may not be the only measure of strength gain, as there have been reports of inconsistencies in the relationship between muscle size and strength. 33 Studies also have shown a greater frequency of the D allele among athletes who compete in shorter-distance events.…”
Section: Ace and Strength Performancementioning
confidence: 99%
See 1 more Smart Citation